COMPARATIVE PUBLIC ADMINISTRATION: THE ESSENTIAL READINGS - Lawrence R. Jones, NANCY S. LIND (Elsevier, 2006)
Comparative Public Administration (CPA) attained its greatest intellectual influence during the post World War II era, although it was utilized much earlier. In 1887, for example, Woodrow Wilson’s article, considered the first articulation of public administration as a field of study, clearly emphasized the comparative approach as the foundation of developing administrative principles. Wilson argued for ‘‘putting away all prejudices against looking anywhere in the world but at home for suggestions’’ in the study of public administration. He emphasized that ‘‘nowhere else in the whole field of politics y, can we make use of the historical, comparative method more safely than in this province of administration’’ (Wilson, 1887). During the early part of the 20th century, Max Weber also differentiated and compared three types of authority system: traditional, charismatic, and legal–rational, producing in the process one of the most influential conceptualizations in social sciences the bureaucratic model. To underscore the attributes of the bureaucratic rational model of administration, Weber compared it to other systems that were prevalent in other times and places. What matters here is that the comparative approach was central to Weber’s theory on authority systems throughout history. The post WWII advance and expansion of comparative administration scholarship was stimulated by contributions from scholars whose intellectual pursuits reached beyond the national boundary of one country, and who managed to bridge the divide between administration and politics.